Pterostilbene improves exercise intolerance induced by sleep restriction in mice by activating AMPK/SIRT1 signaling and promoting mitochondrial biosynthesis - LIU Yang; LANG Hedong; HUI Suocheng; CHEN Ka; MI Mantian (Di-san junyi daxue xuebao, 2020)
Objective To investigate the effect of pterostilbene (PTE) on exercise intolerance induced by sleep restriction (SR) in mice and explore the underlying mechanism. Methods Thirty male C57BL/6J mice were randomized into control group, SR group and SR with PTE treatment (SR+PTE) group. The mice in the latter 2 groups were kept awake using a sleep deprivation apparatus with their daily sleep time limited to 4 h for 5 consecutive days. In SR+PTE group, the mice received PTE treatment by gavage at a daily dose of 100 mg/kg (administered at 08:00 am). After the 5-day treatment, body weight changes of the mice were recorded, and a weight-loaded forced swimming test was performed; blood samples were collected for detecting serum levels of biochemical indicators of exercise fatigue. HE staining was used to observe the pathological changes of the skeletal muscle tissue. The mitochondrial DNA (mtDNA) content and the expressions of AMPK, SIRT1 and mitochondrial biogenesis-related genes were determined by real-time PCR and Western blotting. Results Compared with those in the control group, the mice in both SR and SR+PTE groups showed significant weight loss after the treatment (P < 0.05), and the decrease was more obvious in SR group (P < 0.05). Compared with those in SR group, the mice in SR+PTE group had significantly prolonged exhaustive swimming time and significantly lowered serum levels of LDH and CK (P < 0.05). No significant differences were found in skeletal muscle pathologies among the groups. The mtDNA content and expression levels of mitochondrial biosynthesis-related genes including PGC1α, NRF1, ERRα and TFAM were significantly higher in SR+PTE group than in SR group (P < 0.05). Western blotting showed that the expression levels of p-AMPK and SIRT1 were significantly higher in SR+PTE group than in SR group (P < 0.05), while that of AMPK were comparable between the 2 groups. Conclusion PTE can improve exercise intolerance in mice exposed to SR possibly by activating AMPK/SIRT1 signaling pathway to enhance mitochondrial biogenesis.